Antimicrobial drug sensitivity pattern of Pseudomonas aeruginosa in respiratory infections - Ameen, Syed S.; Prakash, Shanmukananda; K., Laxminarayana Bairy; Soherwardi, Shahabuddin (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pseudomonas aeruginosa, a gram-negative pathogen commonly associated with nosocomial infections is the most widespread multidrug-resistant pathogen causing pneumonia in hospitalized patients. Inadequate empirical therapy has been associated with high mortality and morbidity. Objective: To evaluate and analyze the antimicrobial susceptibility pattern of P. aeruginosa in respiratory infections in a tertiary care hospital. Methods: The study was carried out at Kasturba Hospital, Manipal from Jan 2011 to Dec 2011. Specimens of 63 in-patients were analyzed who were culture positive for P. aeruginosa. Results: Majority of patients were aged above 40yrs with a male preponderance. Specimens were taken from patients who were diagnosed with bronchiectasis, pneumonia, COPD, bronchial asthma etc. Overall the organism was most sensitive to carbapenems (87.3%) followed by cefoperazone-sulbactam combination (85.7%). Sensitivity to ceftazidime and cefepime was equal (82.5%) and was more when compared to piperacillin-tazobactam (81.5%). Overall resistance rate was highest for fluoroquinolones (23.8%) followed by aztreonam (22.2%). Conclusions: Hence we would like to recommend cefoperazone-sulbactam as the preferred antipseudomonal agent and carbapenems as reserved drugs in treating pseudomonal lung infections. Use of fluoroquinolones and aztreonam as monotherapy in resistant P. aeruginosa infections should be restricted.